1987
DOI: 10.1111/j.1432-1033.1987.tb13619.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of murine granulocyte/macrophage-colony-stimulating factor reveals critical residues near the N terminus

Abstract: A number of cDNAs encoding mutant forms of the murine haemopoietic growth factor, granulocyte/macrophage-colony-stimulating factor (GM-CSF), have been derived by in vitro mutagenesis and expressed in simian COS cells. Determination of the biological activity of the mutant factors revealed that residues within the regions 11 -15, 24-37, 47-49 and 81 -89 are required for generating a functional GM-CSF molecule. In particular, truncation of either of two strongly predicted a helices near the N terminus of the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1988
1988
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…The present work and that of Zurawski and Zurawski (22) demonstrate the importance of correlating expression levels of mutant proteins with their corresponding activities. The inability of Gough et al (8) to determine the mutant protein concentrations may explain why none of the critical regions identified in the present work coincide with their results; it is possible that insufficient expression of mutant proteins accounts for their negative assay results. Additionally, their use of large deletions to identify critical regions introduces the potential of gross structural changes that may have resulted in nonspecific inactivation of the mGM-CSF protein.…”
Section: Sequences Between Critical Regions Are Not Essential Forcontrasting
confidence: 58%
See 2 more Smart Citations
“…The present work and that of Zurawski and Zurawski (22) demonstrate the importance of correlating expression levels of mutant proteins with their corresponding activities. The inability of Gough et al (8) to determine the mutant protein concentrations may explain why none of the critical regions identified in the present work coincide with their results; it is possible that insufficient expression of mutant proteins accounts for their negative assay results. Additionally, their use of large deletions to identify critical regions introduces the potential of gross structural changes that may have resulted in nonspecific inactivation of the mGM-CSF protein.…”
Section: Sequences Between Critical Regions Are Not Essential Forcontrasting
confidence: 58%
“…Gough et al (8) have identified residues 11-15, 24-37, 47-49, and 81-89 as required for generating a functional mGM-CSF. The present work and that of Zurawski and Zurawski (22) demonstrate the importance of correlating expression levels of mutant proteins with their corresponding activities.…”
Section: Sequences Between Critical Regions Are Not Essential Formentioning
confidence: 99%
See 1 more Smart Citation
“…RNA Preparation and Northern Blotting-Cytoplasmic RNA was isolated by the procedure of Gough (35) and subjected to Northern blot analysis (36). The blot was probed with an ␣-32 P-labeled full-length STAT1␣/␤ cDNA (a gift from Dr. Chris Schindler, Dept.…”
Section: Methodsmentioning
confidence: 99%
“…These studies indicated a critical role for amino acids 21-31 (A helix) and 77-94 (including the C helix) in mediating the activity of human GM-CSF, suggesting that the second site may be involved in binding to the GM-CSFR␣. Additional mutagenesis studies (42)(43)(44)(45), mapping of neutralizing monoclonal antibodies (46 -50), and synthetic peptide studies (47, 51, 52) suggest other potential interaction sites. Thus, in spite of considerable study, the GM-CSFR␣ interaction site(s) on GM-CSF remain incompletely characterized.…”
Section: Discussionmentioning
confidence: 99%